Analisa Semiotik Makna Motivasi Berkarya Lirik Lagu Zona Nyaman Karya Fourtwenty - Chepi Nurdiansyah (Jurnal Komunikasi, 2018)
This research is entitled Semiotic Analysis Meaning Motivassi Working on "Zona Nyaman" Song Lyrics by Fourtwenty. This study aims to find out the meaning contained in the lyrics of these songs. The theory used and relevant in this study is the Roland Barthes Theory The method in this study uses qualitative methods. The subject of this research is the lyrics of the Zona Nyaman song. Data collection techniques are carried out by conducting object research, dissecting research objects and dying means signs. This study found several conclusions that the meaning contained in the comfort zone song "Empattwenty's work has a motivational member meaning in the life of each temple. In each feed on the song using parables words that can be analyzed in semiotics. keywords: Semiotik, Song lyrics, Motivation to work